Ompok karunkodu, a new catfish (Teleostei: Siluridae) from southern India - Ng, Heok Hee (Zootaxa, 2013)
Ompok karunkodu, a new species of silurid catfish is described from the Amaravathi River, a right-hand tributary of the Kaveri [=Cauvery] River in Tamil Nadu, southern India. Ompok karunkodu can be distinguished from all congeners in the Indian subcontinent in having a markedly convex predorsal profile (vs. with a slight or distinct concavity in the supraethmoidal or supraoccipital region), and a unique combination of the following characters: prognathous lower jaw causing anterior profile of head to appear rounded when viewed laterally, maxillary barbel reaching to base of pectoral-fin spine, eye diameter 13.7% HL, head width 13.0% SL, body depth at anus 14.2% SL, 65 anal-fin rays, caudal peduncle depth 5.0% SL, caudal-fin length 12.6% SL, caudal fin with rounded lobes, 54 vertebrae, and dark midlateral stripe running along sides of body.